Lymphocytic colitis: a distinct clinical entity? A clinicopathological confrontation of lymphocytic and collagenous colitis. Issue 3 (1st September 1999) - Baert, F; Wouters, K; D'Haens, G; Hoang, P; Naegels, S; D'Heygere, F; Holvoet, J; Louis, E; Devos, M; Geboes, K
Abstract : BACKGROUND AND AIMS: It is not known whether lymphocytic colitis and collagenous colitis represent different clinical entities or constitute part of a spectrum of disease. METHODS: Detailed clinical features and histological findings were compared in a large series of patients with confirmed lymphocytic and collagenous colitis. RESULTS: Histological diagnosis was confirmed in 96 patients with collagenous colitis and 80 with lymphocytic colitis. Twenty eight per cent of patients with collagenous colitis and 26% of patients with lymphocytic colitis had overlapping but less pronounced histological features. Both groups were equal in terms of age, use of aspirin and non-steroidal anti-inflammatory drugs, associated autoimmune conditions, arthritis, diarrhoea, and abdominal pain. The male:female ratio was 27:73 for collagenous colitis and 45:55 for lymphocytic colitis (p=0.013). Twenty five per cent of patients with collagenous colitis compared with 14% of patients with lymphocytic colitis were active smokers; only 8.3% of patients with collagenous colitis had stopped smoking compared with 23% of patients with lymphocytic colitis (p=0.013). Drug induced disease was suspected for ticlopidine (two collagenous colitis, four lymphocytic colitis) and flutamide (four lymphocytic colitis). Mean duration of symptoms before diagnosis was two months for lymphocytic colitis and four months for collagenous colitis. Overall prognosis was generally mild; 84% of patients with lymphocytic colitis and 74% of patients with collagenous colitis reported resolution or significant improvement (p=0.033). CONCLUSIONS: Collagenous and lymphocytic colitis are similar but not identical. Patients with lymphocytic colitis present somewhat earlier and are less likely to be active smokers. Symptoms are milder and more likely to disappear in lymphocytic colitis. Ticlopidine and flutamide should be added to the list of drugs inducing colitis.